An ethics of care: PGCE students' experiences of online learning during Covid-19 - Feldman, Jennifer (Critical Studies in Teaching and Learning, 2023)
The article discusses the online teaching and learning experiences of university students during the recent countrywide lockdown and higher education institutional shutdown due to the Covid19 pandemic. Drawing on philosopher Joan Tronto’s phases of care and associated moral elements, the article reports on survey data from a large cohort of students in the Post Graduate Certificate of Education programme at Stellenbosch University and seeks to analyse the students’ care needs and experiences of care during this period. The aim of the article discussion is not to answer the question whether the university institution offered the students good care during the campus shutdown and remote teaching and learning, but rather to understand the experiences of the students of online teaching and learning during this time.